A afetividade na formação de professores universitários, em Licenciaturas, a partir do diálogo entre a Educação e o Direito - Scott Junior, Valmor (2015)
This research aims at understanding, through dialogue between the Law and Education, the impact of affectivity in the training of university teachers. This study is based on the epistemological studies of Humberto Maturana precisely the love of Biology and the Biology of Knowledge. It is a qualitative research, being used as a methodology content analysis. For this, we analyzed courses of pedagogical projects - PPCs, of Undergraduate in the area of Natural and Mathematical Sciences and in Social and Human Sciences, Federal University of Santa Maria - UFSM. The materiality of the survey consists of ten verbs that appear more frequently in these documents, from which an interpretation from two categories will be held: Reading cognitive and affective Reading. As a theoretical basis, it designed a chapter entitled: Dialogue on affection: the right to education to justify the choice of theme. The results and discussion will be drawn from the information extracted from these documents in compliance with materiality (verbs) and categories, with the collaboration of Maturana (1998), Santos (2009), Barcelos (2013), Bauman (1999), Bonavides ( 2005), Dias (2006), Jones (2011), Hilal (1985), Pereira (2006) Milk (2005), among others. The epistemological thread that will guide the research will be studies of Humberto Maturana on the Biology of Knowledge, in collaboration with Arroyo (2001), Freire (1996), among others, and the love of biology and affection as emotion. The formation of the university professor is directly related to the educational process and the development of dimensions that enable learning; among them, affection.